Bridging Theory and Practice: The Implementation of Case-Based Contextual Teaching and Learning in Higher Education - Budiarto, Mochamad Kamil; Nahrowi, Nazli; Alim, Rafii Fathul; Santoso, Alivia Rizky Wulan; Aini, Isna Qurrotun (Universitas Negeri Yogyakarta, 2025)
The shifting paradigm of higher education demands pedagogical innovation that connects theory and practice contextually. This study examines the implementation of the Contextual Teaching and Learning (CTL) model through case study-based assignments to enhance student engagement and critical thinking in the Educational Technology Study Program at PSDKU UNESA. Using a descriptive qualitative design, data were collected through observation, interviews, and document analysis with 87 students during eight lecture sessions. Analysis was conducted using the Miles & Huberman interactive model, which included data reduction, presentation, and verification. The results indicate that learning planning and implementation aligned with CTL principles, which emphasize the link between theory and practice, reflection, and collaboration. Students demonstrated significant improvements in cognitive, affective, and social participation, with positive responses regarding the relevance of learning to professional competencies. Key supporting factors included lecturer readiness, institutional support, and case authenticity, while challenges included limited time and technological resources. These findings confirm the effectiveness of case study-based CTL as an approach that fosters meaningful and workplace-relevant learning and recommend expanding its application to other higher education contexts.